2016
DOI: 10.4018/978-1-4666-9567-2.ch022
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship

Abstract: The purpose of this chapter is to contribute to a better understanding of the link between social entrepreneurship and institutional environment in Portugal. A quantitative approach is used in the study, with primary data collected through an online survey. A questionnaire was emailed to both Portuguese Non-Governmental Organizations and projects available on the Portuguese Social Stock Exchange. In the analysis of the data, we used descriptive statistics, factorial analysis and t-student tests in an attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, evidence of interactions between institutional environments and SE is mixed, reinforcing the conflicting views of advocates of institutional frameworks regarding SE. For instance, in a study to understand the link between SE and the institutional environment in Portugal, Bernardino et al (2016) conclude that a favourable institutional environment has minimal importance in the emergence of SE, implying that SE can flourish even in weak Crisis management in developing economies institutional contexts. But an alternative stream of research investigating the link between institutional environments and SE in developing economies suggest that institutional environments have a positive and significant impact on SE (Urban and Kujinga, 2017;Littlewood and Holt, 2018).…”
Section: Social Entrepreneurship and Institutional Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence of interactions between institutional environments and SE is mixed, reinforcing the conflicting views of advocates of institutional frameworks regarding SE. For instance, in a study to understand the link between SE and the institutional environment in Portugal, Bernardino et al (2016) conclude that a favourable institutional environment has minimal importance in the emergence of SE, implying that SE can flourish even in weak Crisis management in developing economies institutional contexts. But an alternative stream of research investigating the link between institutional environments and SE in developing economies suggest that institutional environments have a positive and significant impact on SE (Urban and Kujinga, 2017;Littlewood and Holt, 2018).…”
Section: Social Entrepreneurship and Institutional Environmentmentioning
confidence: 99%
“…However, evidence of interactions between institutional environments and SE is mixed, reinforcing the conflicting views of advocates of institutional frameworks regarding SE. For instance, in a study to understand the link between SE and the institutional environment in Portugal, Bernardino et al. (2016) conclude that a favourable institutional environment has minimal importance in the emergence of SE, implying that SE can flourish even in weak institutional contexts.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Social entrepreneurship literature suggests that educational institutions can supply courses and graduate degree programs on social entrepreneurship, which may be essential in raising awareness and building a knowledge base; building a social entrepreneurial culture and developing skills; and providing services and creating pathways for development (Bernardino, Santos, & Ribeiro, 2016). Some studies have found that support from universities is highly important for new venture creation, in terms of technical and commercial support, and business advice provided to entrepreneurs (Lockett, Cave, Kerr, & Robinson, 2009).…”
Section: Control Variablesmentioning
confidence: 99%